2018
DOI: 10.1029/2018sw001931
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for Analysis of Power Grid Vulnerability to Geomagnetic Disturbances

Abstract: Multiple power system equipment damage from strong geomagnetic disturbance (GMD) can significantly disrupt power grid operation. This has happened twice: in 1989, in North America and the United Kingdom and, in 2003, in Scandinavia and South Africa. Modern bulk high-voltage power grids were designed more than 60 years ago for achieving more economic benefits in power transfer. In turn, high-voltage, and especially the lately designed ultrahigh-voltage, grids are more vulnerable to GMD. It is anticipated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Knowledge of the installed power system equipment and GIC amplitude alone are not enough to justify ‘pass’ or ‘suffer the damage’. The power system performance analysis in the presence of a GMD showed that it is a multicriteria problem [56]. The results presented here can be a good basis for the ongoing development of mitigation actions.…”
Section: Discussionmentioning
confidence: 78%
“…Knowledge of the installed power system equipment and GIC amplitude alone are not enough to justify ‘pass’ or ‘suffer the damage’. The power system performance analysis in the presence of a GMD showed that it is a multicriteria problem [56]. The results presented here can be a good basis for the ongoing development of mitigation actions.…”
Section: Discussionmentioning
confidence: 78%
“…This is consistent with the observation of Pulkkinen et al (2006) on the linear relationship between the GIC values and the local time variations of the geomagnetic field. Independently, Sokolova et al (2018) performed a preliminary risk analysis of the Siberian unified power grid, based primarily on the network configuration and equipment condition. These authors do not currently invoke electric field estimates or electrical conductivity models in their analyses.…”
Section: Europe: Russiamentioning
confidence: 99%
“…High-amplitude GIC peaks last for several minutes. Power grid vulnerability is a multi-criteria problem [15]. The same power system equipment can be vulnerable in multiple ways depending on the GMD type.…”
Section: Introductionmentioning
confidence: 99%